1998
DOI: 10.1073/pnas.95.4.1618
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular metabolic transients and mitochondrial redox waves in heart cells

Abstract: Precise matching of energy supply with demand requires delicately balanced control of the enzymes involved in substrate metabolism. In response to a change in substrate supply, the nonlinear properties of metabolic control may induce complex dynamic behavior. Using confocal imaging of f lavoprotein redox potential and mitochondrial membrane potential, we show that substrate deprivation leads to subcellular heterogeneity of mitochondrial energization in intact cells. The complex spatiotemporal patterns of redox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
158
1
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(169 citation statements)
references
References 41 publications
8
158
1
2
Order By: Relevance
“…Additional evidence for this proposal came from measuring radiation-induced mitochondrial membrane depolarization and enhanced permeability of the mitochondrial membrane to the fluorescent small molecule, calcein. This model fits with previous findings from other investigators demonstrating such propagating signals within a cell's mitochondrial pool and as a mechanism involved in Ca 2 þ homeostasis and cellular redox modulation (Bernardi and Petronelli, 1996;Vercesi et al, 1997;Ichas and Mazat, 1998;Romashko et al, 1998;Zorov et al, 2000). Specifically, Zorov et al (2000) proposed that ROSinduced ROS release accompanies the mitochondrial permeability transition and provides a 'self-amplifying' mechanism by which redox signals can be transmitted throughout the cell.…”
Section: Gsh Subcellular Compartmentalization and The Redox Status Osupporting
confidence: 75%
See 1 more Smart Citation
“…Additional evidence for this proposal came from measuring radiation-induced mitochondrial membrane depolarization and enhanced permeability of the mitochondrial membrane to the fluorescent small molecule, calcein. This model fits with previous findings from other investigators demonstrating such propagating signals within a cell's mitochondrial pool and as a mechanism involved in Ca 2 þ homeostasis and cellular redox modulation (Bernardi and Petronelli, 1996;Vercesi et al, 1997;Ichas and Mazat, 1998;Romashko et al, 1998;Zorov et al, 2000). Specifically, Zorov et al (2000) proposed that ROSinduced ROS release accompanies the mitochondrial permeability transition and provides a 'self-amplifying' mechanism by which redox signals can be transmitted throughout the cell.…”
Section: Gsh Subcellular Compartmentalization and The Redox Status Osupporting
confidence: 75%
“…This too entails a two-step process with an initial nonspecific oxidative event triggering the second but specific redox sensitive step involving propagation of a reversible mitochondrial permeability transition from one mitochondrion to adjacent mitochondria (e.g. Romashko et al, 1998;Zorov et al, 2000;Leach et al, 2001Leach et al, , 2002. This propagation ultimately results in the Ca 2 þ -dependent activation of constitutive NOS and NO signaling (Leach et al, 2002).…”
Section: Lifetimes Of Radicals and Diffusion Distancesmentioning
confidence: 99%
“…Modulation of the cellular action potential by these metabolic oscillations led us to hypothesize that these oscillations could result in arrhythmias if present in the heart after ischaemia-reperfusion. Subsequently, we identified the mitochondria as the source of the oscillations and observed they involved the synchronized depolarization of the mitochondrial network of almost the entire heart cell (Romashko et al 1998). Based on the observation that ΔΨ m depolarization could either occur in individual mitochondria, clusters of mitochondria, or in the whole network, we suggested that the mitochondria may represent a network of coupled oscillators (Romashko et al 1998).…”
Section: Mitochondrial Criticality and Large Amplitude Oscillation Unmentioning
confidence: 98%
“…Although the transition in the mitochondrial spanning cluster appears abrupt, the phase transition should be slow enough to be resolved as waves of depolarization with faster image acquisition and͞or interventions that slow propagation, as described for spontaneous metabolic oscillations (9). Indeed, at higher temporal resolution, depolarization waves could be detected with a speed of 22 m⅐s Ϫ1 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…At the subcellular level, adapting energy production to meet a variable metabolic demand depends on the coordinated action of thousands of mitochondria in the cardiac myocyte, which are distributed between myofilaments in a lattice-like network of nonlinear elements. This arrangement is conducive to spatiotemporal patterns of self-organization, for instance, oscillations and͞or propagating waves (9,10). However, it is not known how individual mitochondria interact with their neighbors or how metabolic signals are communicated over cellular distances.…”
mentioning
confidence: 99%